Prostatic Leiomyoma: A Case Report - Soufiane Mellas; Ahmed Amine Bouchikhi; Mohammed-Fadl Tazi; Abdelhak Khallouk; Jalal-Eddin Elammari; Mohammed-Jamal El Fassi; Moulay Hassan Farih (Case Reports in Urology)
Prostatic enlargement due to benign adenomatous hyperplasia is very common in elderly males. However, benign mesenchymal tumors especially true leiomyoma of the prostate are rare. We describe a 68-year-old male presenting a urinary obstruction lasting more than two years. The patient was referred for an acute urinary retention. The clinical examination was normal. The perrectal examination revealed an enlarged prostate without abnormalities. An endoscopic resection was performed. The histopathological examination revealed a benign smooth muscle tumor with absence of glandular hyperplasia; the result was confirmed by immunohistochemistry. Accordingly, the diagnosis of true leiomyoma of the prostate was made.